Evidence-Based Brief Psychological Treatment for Emotional Disorders in Primary and Specialized Care: Study Protocol of a Randomized Controlled Trial - Gálvez-Lara, Mario; Corpas, Jorge; Venceslá, José Fernando; Moriana, Juan A. (Frontiers in Psychology, 2019)
Background: Emotional Disorders (EDs) are very prevalent in Primary Care (PC). However, general practitioners (GPs) have difficulties to make the diagnosis and the treatment of this disorders that are usually treated with drugs. Brief psychological therapies may be a new option to treat EDs in a PC context. This article aims to present a study protocol to evaluate the effectiveness and the efficiency of an adaptation to brief format of the “Unified Protocol for the transdiagnostic treatment of EDs”. Methods: This is a single-blinded RCT among 165 patients with EDs. Patients will be randomly assigned to receive brief psychological treatment based on UP, conventional psychological treatment, conventional psychological treatment plus pharmacological treatment, minimum intervention based on basic psychoeducational information, or pharmacological treatment only. Outcome measure will be the following: GAD-7, STAI, PHQ-9, BDI-II, PHQ-15, PHQ-PD and BSI-18. Assessments will be carried out by blinded raters at baseline, after the treatment and six-month follow-up. Discussion: The findings of this RCT may encourage the implementation of brief therapies in the AP context, what would lead to the decongestion of the public health system, the treatment of a greater number of people with EDs in a shorter time, the reduction of the side effects of pharmacological treatment and a possible economic savings for public purse. Trial registration: ClinicalTrial.gov: NCT03286881. Registered 19 September 2017.